From the grain/workpiece interaction to the coupled thermal-mechanical residual stresses: an integrated modeling for controlled stress grinding of bearing ring raceway - Wang, Dexiang; Sun, Shufeng; Jiang, Jingliang; Liu, Xinfu (International journal of advanced manufacturing technology, 2019)
The residual stress distribution in the surface layer of bearing ring raceway has a significant impact on the fatigue life of rolling bearings. Grinding is the critical manufacturing process for bearing rings, and directly determines the residual stress distribution. However, the residual stress distribution is generally not detected in the manufacturing procedure of rolling bearings, and there are no corresponding control standards or measures. This research intensively investigated the grinding mechanism of bearing ring raceway, and performed an integrated modeling to achieve controlled stress grinding. The integrated modeling starts from the grain/workpiece interaction, through modeling of the distributions of interaction stresses and heat flux, and ends up with the numerical model for coupled thermal-mechanical residual stress analysis. The integrated modeling was validated experimentally through the comparisons between the measured and simulated temperatures and residual stresses. With the integrated model, the generating mechanism of the residual stress distribution was revealed, the influences of grinding parameters and cooling conditions were investigated, and the control strategy was finally put forward. The investigations show that grinding can produce compressive residual stresses in the surface layer of bearing ring raceway. Heat flux is still detrimental to the formation of compressive residual stresses, although thermally induced tensile residual stresses are prevented. To produce compressive residual stresses in the surface layer of bearing ring raceway, the rotational speed of bearing ring should be increased, the rotational speed of grinding wheel and the transverse feed speed should be reduced, and increasing convective heat transfer coefficient is more effective than reducing the initial temperature of grinding fluid.